Team rehabilitation services for preschool children with hearing impairment and their mother’s quality of life - Mirahmadi Saeed; Salehi Sousan; Moradi Negin; Habibi Danial (BMC Research Notes)
Abstract Objective Teamwork rehabilitation is recommended for children with hearing impairment, who often require multidimensional support. This study aimed to investigate the impact of team-based rehabilitation services on the quality of life and mental health of mothers of preschool children with hearing impairment. A total of 126 mothers of hearing-impaired children residing in Tehran, Iran, participated in the study. Based on inclusion and exclusion criteria, 63 mothers whose children received team-based rehabilitation and 63 whose children received individual rehabilitation were selected. Participants completed the quality-of-life questionnaire (SF-36) and the Beck Depression Inventory. The results of the two groups were then compared. Results The analysis revealed a statistically significant difference in quality-of-life scores between the two groups (p < 0.05). Additionally, Fisher’s exact test showed that a higher percentage of mothers in the team-based group were categorized as having normal mental health according to the Beck Depression Inventory, compared to the individual-services group. The model of rehabilitation service delivery—team-based versus individual—has a significant impact on maternal depression and quality of life. These findings emphasize the importance of incorporating interdisciplinary approaches in the rehabilitation of children with hearing impairment.